07.11 Contribution of mthfr gene variants in lupus related subclinical atherosclerosis. (1st March 2017) - Giannelou, Maira; Nezos, Andrianos; Maselou, Kyriaki; Drakoulis, Nikolaos; Ioakeimidis, Dimitrios; Koutsilieris, Michael; Moutsopoulos, Haralampos M; Mavragani, Clio P
Abstract : Background: Elevated concentrations of homocysteine have been previously identified as an independent risk factor for subclinical atherosclerosis in patients with systemic lupus erythematosus (SLE). Given that heightened homocysteine levels are known to be strongly influenced by genetic factors, in the current study we investigated the contribution of functional polymorphisms of the gene encoding for the enzyme 5, 10- methylenetetrahydrofolate reductase (MTHFRC677T and MTHFRA1298C) to atherosclerotic disease characterising SLE patients. Materials and methods: 138 consecutive SLE patients, according to the American College of Rheumatology (ACR) classification criteria were included in the study. All patients underwent ultrasound measurement of intima-media thickness scores (IMT) and detection of carotid and/or femoral (C/F) plaque. Clinical, haematological, serological, immunological characteristics, therapeutic regimens and classical risk factors for cardiovascular disease were recorded. Peripheral DNA samples from all SLE patients and 561 age/sex matched apparently healthy volunteers (HC) were genotyped by PCR-based assays for the detection of the MTHFR gene polymorphisms (C677T and A1298C). Data were analysed using univariate and multivariate models (SPSS 21.0) and SNPstats software. Results: While no difference in the prevalence of MTHFR677TT and MTHFR1298CC genotypes were detected between SLE patients and HC (19% vs 18.4% and 9.6% vs 11.9%, respectively, p-values>0.05 for both comparisons), MTHFR677TT variant was detected more frequently in SLE patients with plaque formation and high IMT scores compared to those without (26.8% vs 11.9%, p-value=0.004% and 29% vs 15%, p-value=0.02, respectively). A similar trend-though non significant- was observed between MTHFR1298CC variant with plaque formation/heightened IMT scores. The presence of either MTHFR1298CC or 677TT was identified as independent risk factor for both the formation of atherosclerotic plaque and high IMT scores [OR (95%) CI: 4.8 (1.00–23.7) and OR (95%) CI: 3.6 (1.00–13.8) respectively], following adjustment for potential cofounders. Conclusions: The independent association between the homozygous state for either MTHFR677TT or MTHFR1298CC genetic variants and subclinical atherosclerosis implies genetic influences as potential contributors to the increased burden of atherosclerotic disease characterising SLE.